Strain-Visualization with Ultrasensitive Nanoscale Crack-Based Sensor Assembled with Hierarchical Thermochromic Membrane - Park, Byeonghak; Kim, Jong Uk; Kim, Jisun; Tahk, Dongha; Jeong, Chanho; Ok, Jehyung; Shin, Joo Hwan; Kang, Daeshik; Kim, Tae il (Advanced Functional Materials, 2019)
As eidetic signal recognition has become important, displaying mechanical signals visually has imposed huge demands for simple readability and without complex signal processing. Such visualization of mechanical signals is used in delicate urgent medical or safety-related industries. Accordingly, chromic materials are considered to facilitate visualization with multiple colors and simple process. However, the response and recovery time is very long, such that rapid regular signals are unable to be detected, i.e., physiological signals, such as respiration. Here, the simple visualization of low strain ≈2%, with ultrasensitive crack-based strain sensors with a hierarchical thermochromic layer is suggested. The sensor shows a gradient color change from red to white color in each strain, which is attributed to the hierarchical property, and the thermal response (recovery) time is dramatically minimized within 0.6 s from 45 to 37 °C, as the hierarchical membrane is inspired by termite mounds for efficient thermal management. The fast recovery property can be taken advantage of in medical fields, such as monitoring regular respiration, and the color changes can be delicately monitored with high accuracy by software on a mobile phone.
Keywords: Fast response; Hierarchical structures; Nano scale; Strain visualizations; Thermo-chromic; fast response; hierarchical structures; nanoscale crack-based sensors; strain visualization; thermochromic membranes